2017
DOI: 10.1186/s10194-017-0829-8
|View full text |Cite
|
Sign up to set email alerts
|

The burden of headache is associated to pain interference, depression and headache duration in chronic tension type headache: a 1-year longitudinal study

Abstract: BackgroundTo investigate variables associated at one year (longitudinal design) with the physical or emotional component of burden in chronic tension type headache (CTTH).MethodsOne hundred and thirty (n = 130) individuals with CTTH participated in this longitudinal study. Clinical features were collected with a 4-weeks headache diary at baseline and 1-year follow-up. The burden of headache was assessed at baseline and one -year follow-up with the Headache Disability Inventory (HDI), physical (HDI-P) or emotio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 36 publications
0
10
0
3
Order By: Relevance
“…The current analysis is included as part of a multicenter international headache study. Some patients from the current study were also included in a previous part of the study which data have been already published [ 16 , 17 ]. This study presents new data by including more patients, different outcomes and statistical analysis, and a longitudinal design.…”
Section: Methodsmentioning
confidence: 99%
“…The current analysis is included as part of a multicenter international headache study. Some patients from the current study were also included in a previous part of the study which data have been already published [ 16 , 17 ]. This study presents new data by including more patients, different outcomes and statistical analysis, and a longitudinal design.…”
Section: Methodsmentioning
confidence: 99%
“…Functional magnetic resonance imaging (fMRI) studies also found that stimulating LI4 and LR3 could transform the pain-activated brain regions to the inhibitory state, exert analgesic effects, and relieve physical pain caused by central sensitization [57,58]. Moreover, psychological factor is also known as an important inducement for TTH [59,60]. [61], partly via upregulating hippocampal AMPA receptors [62].…”
Section: Discussionmentioning
confidence: 99%
“…Первинний головний біль зустрічається значно частіше і становить 95-98 % усіх форм цефалгій. Головний біль напруження (ГБН) -найбільш поширений у популяції тип ГБ, що проявляється цефалгічними епізодами тривалістю від декількох хвилин до декількох діб, і становить понад 70 % усіх ГБ [2][3][4][5]. Недавній аналіз тягаря різних форм ГБ показав, що ступінь дезадаптації і соціально-економічних збитків, пов'язаних з ГБН, більший, ніж при мігрені.…”
Section: вступunclassified
“…Недавній аналіз тягаря різних форм ГБ показав, що ступінь дезадаптації і соціально-економічних збитків, пов'язаних з ГБН, більший, ніж при мігрені. ГБН зустрічається частіше за мігрень [5].…”
Section: вступunclassified
See 1 more Smart Citation